Evaluating performance of the operational managers of obstetrics and gynecology service providing wards - Zahra Parvaresh; Ashraf Kazemi; Soheila Ehsanpour; Haniye Sadat Sajadi (Wolters Kluwer Medknow Publications, 2016)
Background: The goal of hospitals, as the most important health care providing centers, is to improve the health level of the society. Achieving this goal is directly related with performance of the managers. This study was conducted to evaluate the performance of operational managers of obstetrics and gynecology service providing wards from the point of view of the staff at educational hospitals of Isfahan University of Medical Sciences in 2015. Materials and Methods: In this descriptive study, target population comprised all supervisors and the staff working at obstetrics and gynecology and maternity wards. Data were collected through a researcher-made questionnaire after evaluation of its reliability and validity using questions on managerial performance (planning, organizing, leadership, and control dimensions) and demographic characteristics of the managers and staff. Data were analyzed using independent t-test, one sample t-test, Spearman and Pearson coefficient tests, and one-way analysis of variance. Results: The total mean score of staff's point of view toward performance of managers' performance was significantly higher than the average level (P < 0.001, t = 13.2). In addition, mean scores of managerial performance in planning (P < 0.001, t = 14.93), organizing (P < 0.001, t = 11.64), leadership (P < 0.001, t = 11.16), and control (P < 0.001, t = 13.75) dimensions were significantly higher than the moderate level. Conclusions: With respect to the fact that maintaining and improving the health of mothers and neonates depends on the management and managers' performance in obstetrics and gynecology service providing wards, more than moderate managers' performance need to be improved. It is recommended that higher-level managers pay special attention to the empowerment of managerial skills among operational managers.